Irom Sharmila's Struggle against Military Repression: A Critique. Issue 2 (December 2016) - Haksar, Nandita
This article argues that although Irom Sharmila's 16-year-old fast from November 2000 to August 2016 has earned her the status of an icon of non-violent protest, yet she did not seek these appellations; her only aim was to put moral pressure on the government to repeal the Armed Forces (Special Powers) Act, 1958. The article seeks to assess the efficacy of Irom Sharmila's protest and how far it has helped or hindered in mobilizing public opinion against the Act. It propounds that the publicity around Irom Sharmila put her on a pedestal and trapped her in her own image, made invisible entire histories of sufferings of people in the northeast, including Manipur, and their struggles against the Armed Forces (Special Powers) Act. The gains of many struggles and efforts were wiped out of the collective memory of the nation and the only image of Manipur was this frail woman with a tube hanging from her nose. The article also argues that there is a kind of fetish in the way the media celebrates non-violence without reference to the political context.